2009
DOI: 10.1186/1750-1326-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular amyloid formation in muscle cells of Aβ-transgenic Caenorhabditis elegans: determinants and physiological role in copper detoxification

Abstract: Background: The amyloid β-peptide is a ubiquitous peptide, which is prone to aggregate forming soluble toxic oligomers and insoluble less-toxic aggregates. The intrinsic and external/ environmental factors that determine Aβ aggregation in vivo are poorly understood, as well as the cellular meaning of this process itself. Genetic data as well as cell biological and biochemical evidence strongly support the hypothesis that Aβ is a major player in the onset and development of Alzheimer's disease. In addition, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 72 publications
6
35
0
Order By: Relevance
“…We previously reported that copper treatment increases the number and size of amyloid deposits in this model (Minniti et al, 2009). At the time, we also showed some data that hinted at the possibility of copper being able to ameliorate the motility impairments in A␤ transgenic C. elegans.…”
Section: Copper Treatment Improves Synaptic Function In A␤ Transgenicsupporting
confidence: 64%
See 3 more Smart Citations
“…We previously reported that copper treatment increases the number and size of amyloid deposits in this model (Minniti et al, 2009). At the time, we also showed some data that hinted at the possibility of copper being able to ameliorate the motility impairments in A␤ transgenic C. elegans.…”
Section: Copper Treatment Improves Synaptic Function In A␤ Transgenicsupporting
confidence: 64%
“…Transgenic C. elegans expressing A␤ show synaptic defects Under normal culture conditions, we previously observed that adult worms expressing A␤ constitutively move significantly slower than the controls that do not express A␤ (Minniti et al, 2009). We hypothesized that the compromised motility of A␤ transgenic worms in liquid medium could be, at least in part, the result of A␤-induced defects at the neuromuscular junction (NMJ), leading to synaptic transmission failure and decreased motor capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These deposits co-localise with amyloid-specific dyes, and display a fibrillar ultrastructure [147,148]. This model (strain CL2006) was used to show that specific point mutations in Aβ can affect the formation of the amyloid deposits [147,149], that Aβ interacts with and induces the expression of the HSP-16 family of heat-shock proteins [150,151], and that daf-2(RNAi) and dietary restriction can both reduce Aβ toxicity [152,153].…”
Section: Inclusion Body Myositismentioning
confidence: 99%